BASIC FINANCIAL TRAINING FOR SMEs ACTORS IN RUMAH HASANAH COMMUNITY BANDUNG - Akbar, Aldi; Madiawati, Putu Nina; Artadita, Sherly (PT. Jurnal Center Indonesia Publisher, 2025)
Financial management training for small and medium enterprises is very relevant in overcoming the challenges faced by new business owners, especially in the Rumah Hasanah community as the target community. With a focus on financial management, this training aims to provide an in-depth understanding of how to build a new business in terms of financial management so that the business can run effectively. This activity considers the limited resources often faced by new businesses, such as limited budgets and lack of experience in financial administration issues. To overcome this gap, this accounting training uses an Android platform-based application, namely the SME Accounting Application from developer Wiinfeel. Thus, SMEs can get updated financial accounting knowledge as well as improve the skills of recording financial transactions so that their digital financial literacy level increases. The results of this training received a very positive response from the participants because they could gain new understanding and experience related to basic financial concepts and effective financial management techniques. And as much as possible they want similar activities to be carried out on an ongoing basis in the future.